Design and synthesis of spirooxindole–pyrrolidines embedded with indole and pyridine heterocycles by multicomponent reaction: anticancer and in silico studies. (12th May 2022) - Mayakrishnan, Sivakalai; Kathirvelan, Devarajan; Arun, Yuvaraj; Saranraj, Krishnan; Balachandran, Chandrasekaran; Aoki, Shin; Yuvaraj, Pannerselvam; Maheswarai, Narayanan Uma
Abstract : We report the synthesis of spirooxindole–pyrrolidines tethered with indole and pyridine heterocycles using 1, 3-dipolar cycloaddition, and their anticancer activities and molecular docking studies. Abstract : Owing to the downsides of existing anticancer drugs, it is necessary to find more effective and selective anticancer agents for researchers in medicinal chemistry worldwide. Spirooxindoles are poised as privileged scaffolds because they exist in many natural products and bioactive molecules. Herein, we report an efficient, environment-friendly route for synthesizing a series of spirooxindoles using the 1, 3-dipolar cycloaddition reaction of a dipolarophile with in situ generated azomethine ylide using ethanol as a solvent without any catalyst. The reaction offers potent biologically active spirooxindole fused with indole and pyridine heterocycles in good to excellent yield (69–94%) with higher diastereoselectivity. These synthesized compounds (4a–x ) were screened for anticancer activity using A549, HepG-2, and SKOV-3 cancer cell lines using the MTT assay. Among all the screened compounds, 4u and 4w displayed substantial cytotoxic activity against HepG-2 cells at less than 10 μg mL −1 . Molecular docking studies with the Bcl-2 and ALK receptor revealed that the higher binding energy was observed for 4u and 4w, and 4c and 4o with a value of −6.56 and −8.41, −6.73, and −7.14 kcal mol −1, respectively. Considering all the data, compounds 4u and 4w, 4c and 4o possess potent anticancer activity against respective receptors and can be the promising lead compounds for cancer drug discovery.